980-nm, 15-W cw laser diodes on F-mount-type heat sinks. (28th December 2015) - Bezotosnyi, V V; Krokhin, O N; Oleshchenko, V A; Pevtsov, V F; Popov, Yu M; Cheshev, E A
Abstract: We have studied the key optical emission parameters of laser diodes (emission wavelength, 980 nm; stripe contact width, 95 μm) mounted directly on F- and C-mount-type copper heat sinks, without intermediate elements (submounts). When effectively cooled by a thermoelectric microcooler, the lasers on the F-mount operated stably at output powers up to 20 W. The lasers were tested for reliable operation at an output power of 15 W for 100 h, and no decrease in output power was detected to within measurement accuracy. The experimentally determined maximum total efficiency is 71.7% and the efficiency at a nominal output power of 15 W is 61%. We compare parameters of the laser diodes mounted on C- and F-mounts and discuss the advantages of the F-mounts.